Perception of Life Quality of Individuals with Periodontal Disease during Covid-19 Pandemic in Brazil (International Journal of Scientific Research and Management (IJSRM), 2022)
In January 2020, the World Health Organization identified COVID-19, caused by the SARS-CoV-2 virus, as a global health emergency. Restrictive measures and uncertainties resulted in a time of high stress, anguish, anxiety, depression and other psychosomatic symptoms. Studies have indicated that oral health was affected by the increased frequency of caries, bruxism and periodontal disease related to the COVID-19 pandemic. The aim of this research was to evaluate the impairment of quality of life of individuals aged between 20 and 70 years, diagnosed with periodontal disease during the COVID-19 pandemic. Material and methods: After the approval of Ethics and Research, the data collection was done by online questionnaire, built on the Google Forms platform® and disclosed to periodontist dentists. The form was original multithematic containing 25 semi-structured questions, which were divided into sociodemographic questions and objective and subjective questions, according to the norms of resolution 510/16 (BRAZIL, 2016). The questionnaire was accessible for 3 months between June and September 2021. As a result, 125 responses were obtained, 14 of which were excluded: 13 because they corresponded to those over 70 years of age and 01 because the patient did not state age. The total number of valid answers was 111. It can be concluded that the COVID-19 Pandemic contributed to the impairment of quality of life and the appearance of oral alterations, bruxism and intensification of previously existing problems such as periodontal disease, mainly due to inadequate or insufficient self-care practices.